Single Nucleotide Polymorphism; A Molecular Marker for Genetic Variations - Nayyar, Ayesha (International Journal of Pathology, 2021)
Objective: Single nucleotide polymorphisms are the most common genetic variations in a human DNA. The aim of the study was to determine the genotype frequency of single nucleotide polymorphisms by a simple PCR technique in order to find the genetic variations in general population.Design: Descriptive study. Place and Duration: It was conducted at Genetic Resource Centre Lab Rawalpindi from Oct 2017- May 2018.Methods: A total of hundred unrelated healthy individuals were selected and assessed for the genotype frequency of eighteen biallelic single nucleotide polymorphisms. Extraction of DNA was done from the whole blood and single nucleotide polymorphism were amplified by using conventional PCR assay. Electrophoresis was carried out and 6% polyacrylamide gels were used for the resultant amplified DNA products.Results: A positive reaction was shown by a discrete band of DNA on the polyacrylamide gel. The most commonly found SNPs were S01, S03, S06, S07a, and S10a.Conclusion: Our results demonstrate the successful screening and genotype frequency of each single nucleotide polymorphism by using a PCR amplification of polyacrylamide gel electrophoresis in general population. This research has provided a new and comprehensive methodology for carrying out further studies using SNPs as a marker of discrimination in the donor/recipient pairs having undergone haematopoietic stem cell transplantation in Pakistan. This PCR assay of SNPs appears to be a simple, rapid, reliable and technically feasible method for a use in a lab equipped with PCR.